Lighting control system using Photoresistor - Rathi Malar Ramalingam (Universiti Malaysia Perlis, 2009)
Energy saving from the use of daylighting in commercial buildings is realized through implementation of photoelectric lighting controls that turns on and off electric lights when sufficient daylight is available to provide adequate work plane illumination. The switching on and off of electronic lighting is based on the signal of a photosensor. The main aim of this project is to create a lighting control system using a photoresistor and subsequently save energy. The sensitivity of the photoresistor in the circuit enables sufficient daylight to take the place of electric light, and then respond by turning off fixture and to eliminate wasted or unwanted electricity. The circuit consists of six main components i.e. a sensing device (photoresistor), a voltage divider (resistors), a comparing circuit (op-amp comparator), an integrator circuit (op-amp integrator), switching circuit (transistors) and the output (LED).